Pedagogical Content Knowledge and the Nepali English Language Teacher Training - Kshetree, Arun Kumar (Journal of Tilottama, 2023)
The paper attempts to explore the crucial role of Pedagogical Content Knowledge (PCK) within the realm of English language teacher training in Nepal. PCK serves as a vital bridge between teachers’ Content Knowledge (CK) and Pedagogical Knowledge (PK), facilitating effective teaching practices and enhancing student learning outcomes. The study examines the interconnectedness of PK, CK, and PCK, with the aim of improving the quality of teacher preparation programs and ultimately, the English language education system in Nepal. Through an extensive literature review, the research establishes a theoretical foundation, examining the conceptual framework of PCK and its significance in teacher education. It identifies existing gaps and challenges in current Nepalese English language teacher training practices, emphasizing the need for the seamless integration of PK, CK, and PCK in classroom instruction. The paper concludes that the contents of the teacher education and training programs differed from what the experts thought should be given. The broader areas of subject matter become narrower in the TPD program in Nepal. However, the nature of the programs is also responsible for the type of content being tried to be imparted to the English teachers. The research identified various factors influencing the successful implementation of PCK in teacher training. These included limited emphasis on PCK in the curriculum, time and resource constraints, and a lack of alignment between teacher education institutions and school practices. The findings underscored the importance of curriculum reforms and the provision of ongoing professional development opportunities to strengthen PCK integration.